From white to yellow : the Japanese in European racial thought, 1300-1735 - Kowner, Rotem (McGill-Queen's studies in the history of ideas, 2014)
When Europeans landed in Japan they encountered people they perceived as white-skinned and highly civilized, but these impressions did not endure. Gradually the Europeans' positive impressions faded away and Japanese were seen as yellow-skinned and relatively inferior. This book traces racial roots of the modern clash between Japan and the West.